2000
DOI: 10.1063/1.480929
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond fluorescence upconversion studies of barrierless bond twisting of auramine in solution

Abstract: Femtosecond fluorescence upconversion studies have been performed for auramine ͑a diphenylmethane dye͒, dissolved in ethanol, as a function of temperature. It is found that the ͑sub͒picosecond decay components in the fluorescence slow down as the temperature is lowered from 293 K to 173 K. From the observation of a residual fluorescence, with a viscosity-dependent lifetime of about 30 ps ͑or longer at higher viscosity͒, and transient absorption results it is concluded that the two-state sink function model ͓B.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
182
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(197 citation statements)
references
References 61 publications
15
182
0
Order By: Relevance
“…[4][5][6]12 The fluorescence enhancement is attributed to the suppression of a competing double-bond isomerization reaction, the rate of which is influenced by the local viscosity. [13][14][15][16] Consistent with their long history of use, the low-energy electronic excitations of dyes such as in Scheme 1 were an early target of quantum mechanical modeling efforts. [17][18][19][20][21] A consistent theme is the notion of resonance between "canonical" valence-bond states with opposing charge localization and bond alternation (cf.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6]12 The fluorescence enhancement is attributed to the suppression of a competing double-bond isomerization reaction, the rate of which is influenced by the local viscosity. [13][14][15][16] Consistent with their long history of use, the low-energy electronic excitations of dyes such as in Scheme 1 were an early target of quantum mechanical modeling efforts. [17][18][19][20][21] A consistent theme is the notion of resonance between "canonical" valence-bond states with opposing charge localization and bond alternation (cf.…”
Section: Introductionmentioning
confidence: 99%
“…20,51,52 It has been remarked that the fluorescence decay times of fluorescent protein chromophore models in different protonation states can vary by up to an order of magnitude. 53 This effect cannot be accounted for by a purely viscosity-dependent mechanism (as has been invoked in other systems 40,42,45 ), because titration should not significantly change the molecular volume nor the surface area. 22 A study of a wide range of different chemical derivatives indicated that several mechanisms may be active, including internal conversion by largeamplitude motion but also possibly hydrogen-bond-assisted decay and/or charge-transfer, depending upon the derivative and the solvent used.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior is predicted by very simple and general theoretical considerations. 31,32 It has not received much attention in the discussions of spectroscopic experiments, wherein it is often assumed that the dynamics can be described by a single effective coordinate [40][41][42][43]45 In order to identify whether twist-dependent charge transfer behavior and pathway bifurcation effects are relevant to understanding the twisting dynamics of monomethines, it is necessary to formulate simple physical models that can describe these phenomena for a general case. This is the point of this paper.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations